INNOVATION AND DEVELOPMENT OF TRUSMI BATIK: IMPROVING SKILLS AND PRODUCTION CAPACITY TO EMPOWER YOUNG CRAFTSMEN IN CIREBON - Mohammad Rezza Fahlevvi; Nur Azizah Heriyani Putri (ipdn, 2025)
Despite its strong cultural value, the Batik Trusmi industry in Cirebon faces challenges in competing globally due to limited knowledge of digital marketing and branding. This study aims to analyze the role of modern marketing in enhancing the competitiveness of Batik Trusmi and to identify the need for digital marketing training among artisans to promote their products internationally. A qualitative approach was used, involving in-depth interviews with 20 artisans and industry stakeholders and a literature review. The findings indicate that while Batik Trusmi artisans possess strong technical skills, they lack knowledge in digital marketing and branding, which hinders expansion into global markets. The recently inaugurated Digital Batik Trusmi Museum is expected to serve as a platform for enhancing the global visibility of Batik products. The implications of this study highlight the importance of strengthening training in digital marketing and branding to boost Batik Trusmi's competitiveness in international markets. This study recommends closer collaboration between the government, the private sector, and artisans to create a digital ecosystem supporting Batik Trusmi's development as a global product.